2007
DOI: 10.1094/pdis-91-9-1194
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Relative Prevalence of Distinct Caulimoviruses (Genus Caulimovirus, Family Caulimoviridae) Associated with Dahlia Mosaic in Dahlia variabilis

Abstract: Dahlia mosaic, caused by Dahlia mosaic virus (DMV), is one of the most important viral diseases of dahlia. Molecular characterization of DMV showed the association of two distinct caulimoviruses (DMV-D10, DMV-Portland) and a D10-like sequence variant (DMV-Holland) with the disease. Using primers specific to these two viruses and the sequence variant, a polymerase chain reaction–based assay was used to determine their relative incidence in several dahlia samples from the United States and the Netherlands. Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In addition to DMV, it was recently shown that there are at least two more distinct caulimoviruses associated with dahlia. Tentatively referred to as Dahlia common mosaic virus (DCMV) and DMV‐D10 (Pahalawatta et al. , 2007; Pappu et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to DMV, it was recently shown that there are at least two more distinct caulimoviruses associated with dahlia. Tentatively referred to as Dahlia common mosaic virus (DCMV) and DMV‐D10 (Pahalawatta et al. , 2007; Pappu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Both DCMV and DMV‐D10 were found to be widespread based on surveys conducted in the USA and Europe (Pappu et al. , 2005; Pahalawatta et al. , 2007; Eid et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMV-D10 shares limited sequence similarity with known caulimoviruses, including DMV, although the genome organization clearly suggests that it is a member of Caulimovirus (Pahalawatta et al, 2008a). DMV-D10 was found to be widespread based on the surveys conducted in the United States and Europe (Pahalawatta et al, 2007;Pappu et al, 2005). Moreover, Pahalawatta et al (2008b) reported that the genome of DMV-D10 is integrated into the dahlia genome and the virus exists as an endogenous plant pararetroviral sequence (EPRV).…”
mentioning
confidence: 99%
“…Previous surveys for the caulimoviruses used partial sequences of DCMV (referred to as DMV-Holland in Pahalawatta et al, 2007) and results showed differences in relative incidence of the three caulimoviruses in the United States and The Netherlands. After the complete genome characterization of DCMV, it becomes evident that there are at least three distinct caulimoviruses that are associated with dahlia mosaic.…”
mentioning
confidence: 99%